2011
DOI: 10.1038/ijo.2010.279
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of abdominal adiposity, waist circumference and body mass index in patients with intermediate-risk prostate cancer treated with radiotherapy

Abstract: Objective: We tested the potential role of abdominal visceral (VAT) and subcutaneous (SAT) adipose tissues, waist circumference (WC) and body mass index (BMI) as prognostic factors in patients with intermediate-risk prostate cancer (clinical stage T1b-2b, and Gleason Score (GS) ¼ 7 and prostate-specific antigen PSA level o15 ng ml À1 , or GS p6 and PSA between 10 and 20 ng ml À1 ) treated with ultrasound-based image-guided radiotherapy. Methods: VAT, SAT and WC (measured from planning abdominal computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…However, the role of adipose tissue distribution in prostate cancer outcomes is less clear. One study of 112 eligible men treated with radiotherapy found that there was no association between obesity measures (visceral and subcutaneous adipose tissues, WC, or BMI) and biochemical failure 19 . Consistent with this study, we found no significant association between overall, visceral, subcutaneous or pelvic adiposity measures and risk of recurrence, prostate cancer‐specific mortality, or all‐cause mortality.…”
Section: Discussionsupporting
confidence: 88%
“…However, the role of adipose tissue distribution in prostate cancer outcomes is less clear. One study of 112 eligible men treated with radiotherapy found that there was no association between obesity measures (visceral and subcutaneous adipose tissues, WC, or BMI) and biochemical failure 19 . Consistent with this study, we found no significant association between overall, visceral, subcutaneous or pelvic adiposity measures and risk of recurrence, prostate cancer‐specific mortality, or all‐cause mortality.…”
Section: Discussionsupporting
confidence: 88%
“…VFA and SFA were calculated using the Eclipse ™ automatic area tool on a single CT slice at the level of L4/L5, as previously described [15] (Figure 1). Since waist circumference (WC) was not measured among these patients in clinic, we determined it retrospectively from the same CT slice as for VFA and SFA.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity was reported to be associated with higher prostate cancer grade at diagnosis [12, 13], increased tumor volume at radical prostatectomy [14, 15] as well as with higher recurrence rates [16]. Abdominal adiposity, waist circumference and BMI were also associated with greater prostate volume as well as younger age at diagnosis [17]. In addition, mortality from prostate cancer has been reported to be increased with elevated body weights [18]; however, other studies have not found this [17].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal adiposity, waist circumference and BMI were also associated with greater prostate volume as well as younger age at diagnosis [17]. In addition, mortality from prostate cancer has been reported to be increased with elevated body weights [18]; however, other studies have not found this [17]. In an examination of a recent meta-analysis of prostate cancer as it related to obesity, it was found that a 5 kg/m 2 increase in BMI was associated with a 15–20% higher risk of dying of prostate cancer depending on what type of study was conducted and a 21% increased chance of biochemical relapse [19].…”
Section: Introductionmentioning
confidence: 99%